Pengembangan Multimedia Interaktif Hewan Berbisa dengan Metode Multimedia Development Life Cycle - Dasril Aldo; Miftahul Ilmi; Hariselmi Hariselmi (Journal of Information System Research (JOSH), 2023)
The problem that is the main focus of this research is the lack of interesting interactive multimedia-based educational information media as a provider of information about venomous animals. This information should also be a concern because these venomous animals are very dangerous, especially for children who still lack information about this. The aim of this research is to become a source of educative information to the public, especially children, about venomous animals as attractive as possible and easy to use. Interactive multimedia is one solution to this problem. The Multimedia Development Life Cycle method is used as a guide in building interactive multimedia with the stages of Concept, Design, Material Collecting, Assembly, Testing and Distribution. From the results of testing in alpha testing all the features in this interactive multimedia can run well. With the results of beta testing on 30 respondents, they get a rating of 4.54 out of 5, so this interactive multimedia is very good and suitable for use as an educative information medium about venomous animals.